Access to drinking water in indigenous communities of Perú in the framework of the state of national emergency - Cacñahuaray Mitma, Ruth Nadhiesda (Universidad Nacional del Litoral, 2020)
This article shows the situation of access to water in a group of indigenous communities in Loreto region, within the framework of the state of national emergency due to the spread of Covid-19. The first section describes the conditions of access to water; then, the regulatory water regime is exposed, in order to determine if the conditions in those communities are property. Finally, a brief reflection is made on the aspects that need to be evaluated and implemented in order to face emergency situations.